African Digital Research Repositories: Mapping the Landscape - Bezuidenhout, Louise; Havemann, Jo; Kitchen, Stephanie; De Mutiis, Anna; Owango, Joy; Zeni, Kevina (My University, 2020)
This data set accompanies the text at doi 10.5281/zenodo.3732273. // Correspondence: JH: info@africarxiv.org, SK: sk111@soas.ac.uk Visual Map: https://kumu.io/access2perspectives/african-digital-research-repositories Dataset: https://tinyurl.com/African-Research-Repositories Archived at https://info.africarxiv.org/african-digital-research-repositories/ Submission form: https://forms.gle/CnyGPmBxN59nWVB38
AfricarXiv in collaboration with the International African Institute (IAI) presents an interactive map of African digital research literature repositories. This drew from IAI’s earlier work from 2016 onwards to identify and list Africa-based institutional repositories that focused on identifying repositories based in African university libraries. Our earlier resources are available at https://www.internationalafricaninstitute.org/repositories. The interactive map extends the work of the IAI to include organizational, governmental, and international repositories. It also maps the interactions between research repositories. In this dataset, we focus on institutional repositories for scholarly works, as defined by Wikipedia contributors (March 2020). Objective The map of African digital repositories was created as a resource to be used in activities addressing the following aims: Improving the discoverability of African research and publications. Enhance the interoperability of existing and emerging African repositories. Identify ways through which digital scholarly search engines can enhance the discoverability of African research. We promote the dissemination of research-based knowledge from African repositories as part of a bigger landscape that also includes online journals, research data repositories, and scholarly publishers to enhance the interconnectivity and accessibility of such repositories across and beyond the African continent and to contribute to a more granular understanding of the continent’s scholarly resources. Data archiving and maintenance. The map and corresponding dataset are hosted on the AfricArXiv website under ‘Resources’ at https://info.africarxiv.org/african-digital-research-repositories/. The listing is not exhaustive and therefore we encourage any repositories relevant for the African continent not listed here to the submission form at https://forms.gle/CnyGPmBxN59nWVB38, or to notify the International African Institute (email sk111@soas.ac.uk). Both AfricArXiv and IAI will continue to maintain the list of repositories as a resource for African researchers and other stakeholders including international African studies communities.
Keywords: Data visualisation; Africa; Repository